Analysis of Students' Image Concept in Constructing Proof And Solving Mathematical Problems Seen From A Gender Perspective - Risya Indriyanti Surya; Edi Syahputra; Mulyono (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the use of students' concept images in constructing proofs and solving mathematical problems. This study uses a qualitative approach with a grounded theory method. This study was conducted at SMA Swasta Pembangunan Galang, with a population of 20 students and a sample of 10 male and 10 female students in grade XI. Research data were obtained through analysis of student work, mathematical proof and problem-solving ability tests, and the interpretation of students' thinking processes across high, medium, and low ability categories. The results of the study indicate that the concept image has an important role in helping students understand concepts, construct proofs, and solve mathematical problems. Students who have a good concept image tend to absorb material more easily, are more active in the learning process, and have a deeper understanding of concepts. In addition, mastery of the concept image also contributes to strengthening students' retention of mathematical material. In addition, this study found differences in the use of the concept image between male and female students, especially in determining the initial steps, using mathematical language, and employing strategies for presenting solutions to mathematical problems.